2022
DOI: 10.1186/s12871-022-01802-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential influence of anaesthesia techniques on the recurrence and progression after resection of non-muscle-invasive bladder cancer: a propensity score-matched analysis

Abstract: Background The non-muscle-invasive bladder cancer is a common malignancy of the urinary system. Many patients relapse after transurethral resection surgery. Different anaesthesia techniques may influence a patient’s immune system during the perioperative time. In this study, we examined the effects of different anaesthesia techniques on the prognosis of primary non-muscle-invasive bladder cancer after transurethral resection surgery. Methods In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Two literatures, comprising 300 subjects, compared cancer progression between two groups [14,16]. No signi cant association was found between RA or GA and the progression of NMIBC (RR = 1.14, 95%CI = 0.71-1.84, P = 0.589,Fig.…”
Section: Progressionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two literatures, comprising 300 subjects, compared cancer progression between two groups [14,16]. No signi cant association was found between RA or GA and the progression of NMIBC (RR = 1.14, 95%CI = 0.71-1.84, P = 0.589,Fig.…”
Section: Progressionmentioning
confidence: 99%
“…When subgroup analyses [14][15][16][17][18]20] were performed based on the speci c types of RA [14][15][16][17][18]20], we found that spinal anesthesia signi cantly reduced the recurrence of NMIBC (RR = 0.80, 95%CI = 0.72-0.88, P < 0.001, Supplemental Fig. 1).…”
Section: Subgroup Analysis Of Type Of Ra and Risk Of Nmibcmentioning
confidence: 99%
See 3 more Smart Citations